Didáctica con Enfoque Intercultural para el Aprendizaje de Matemática - Guacho Tuquinga, Nataly Elizabeth (2024)
The objective of this research work is to develop a guide to teaching strategies with an intercultural approach for learning mathematics in Second Year students of the Unified General Baccalaureate of the Intercultural Bilingual Community Educational Unit Héroes del Cenepa. The applied methodology had a mixed approach with a non-experimental design because the variables were not manipulated under any circumstances, in addition to being descriptive-propositive, since it sought to describe the different strategies and propose a solution to the problem identified regarding the reduced adaptation of Teaching materials to meet the specific cultural needs of students. Through field research, the instrument was applied, which was a structured questionnaire which was used within the classroom to collect the necessary data. It is also transversal, since it was carried out during a specific period. The study population corresponds to seventeen second year high school students and two teachers. Among the main findings, heuristic strategies are identified to strengthen mathematics learning; it is also intended to promote the cultural value and critical thinking of students through the application of teaching strategies with an intercultural approach through the MOSEIB model. The teaching materials suggested in the guide must be appropriate to the cultural realities of the students. It is suggested that teachers integrate local elements and traditions in mathematical activities.